The Back-Door to Prison: Waiver Reform, Blended Sentencing, and the Law of Unintended Consequences - Feld, Barry C (2001)
The Minnesota innovation, Extended Jurisdiction Juvenile Prosecution (EJJ), allowed judges simultaneously to impose a delinquency disposition and an adult criminal sentence, the execution of which the judge stayed pending successful completion of the delinquency sentence. Podkapacz and Feld analyze the implementation of Minnesota's new EJJ blended sentencing law in Hennepin County, the largest metropolitan county in the state